Axial Strain Accelerations Approach for Damage Localization in Statically Determinate Truss Structures. (13th February 2017) - Blachowski, Bartlomiej; An, Yonghui; Spencer, Billie F.; Ou, Jinping
Abstract: This work proposes an efficient and reliable method for damage localization in truss structures. The damage is localized on the basis of measured acceleration signals of the structure followed by simple statistical signal processing. It has three main advantages over many existing methods. First, it can be directly applied to real engineering structures without the need of identifying modal parameters or solving any global optimization problem. Second, the proposed method has higher sensitivity to damage than some other frequently used methods and allows to localize damage as small as a few percentages. Third, it is a model‐free method, which does not require precise finite element model development or updating. Validation of the method has been conducted on numerical examples and laboratory‐scale trusses. Two types of frequently used trusses have been selected for this study, namely, Howe and Bailey trusses. The presented experimental validation of the method shows its efficiency and robustness for damage localization in truss structures.